Assessment of postharvest soil fungal population with special reference to Trichoderma in eggplants - Shirin, A; Md Hossain, -; Rashid, MH Ar; Meah, MB (Progressive Agriculture, 2021)
The research work was done to assess the postharvest soil fungal population and to find out the relation between population dynamics of Trichoderma and soil borne disease of 41 eggplant cultivars. Soil samples collected from IPM lab germplasm maintenance field at post-harvest stage were analyzed for microbes in dilution plate technique. Fungal colonies appeared in each plate were counted and made their average. Incidence and severity of Fusarium wilt and Sclerotium collar rot in the plot of 41 eggplant varieties were recorded at flowering-fruiting stage. The highest total soil fungal population was estimated from the plot soil of eggplant var. Singnath S (IPM- 42) that was 40.75×104. The var. Bijoy had the lowest fungal population that was 7.5×104. A comparison between Trichoderma population and other fungal population was made. Different eggplant cultivars had variation in the population of two important soil fungi- Trichoderma and Fusarium. The total populations of Trichoderma and Fusarium in the plot soil of 41 eggplant varieties were 129.75 and 348.75 × 104 per gram of soil, respectively. The average number of colonies of Trichoderma varied with the range (1-8.25) per plate. Fusarium varied with the range from (2-22.50). In 20 important eggplant varieties out of 41, both Fusarium wilt and Sclerotium collar rot incidence ranged between 0.00 to 40.00%. The variety Puta begun had the highest incidence of Fusarium wilt with the highest soil population of Fusarium oxysporum against the absence of Trichoderma harzianum. The disease incidence at flowering-fruiting stage was negatively correlated with the population of Trichoderma. Disease severity decreased with the increase in Trichoderma population. Increase of Trichoderma population, decreased the population of other fungi (Fusarium oxysporum and Sclerotium rolfsii). These results are clearly indicating that Trichoderma might have the antagonistic potential and might contribute to the reduction of incidence of soil-borne diseases. Progressive Agriculture 32 (1): 31-42, 2021